The Financial Monitoring: Assessing the Risk Profile of an Auditing Firm - Lubenchenko О. Е. (Statistics of Ukraine, 2024)
The article is devoted to vital issues of performing the initial financial monitoring by specially assigned entities of initial financial monitoring. It contains a review of the requirements fixed in the Decree of the Ministry of Finance of Ukraine No. 465 “Approval of Criteria for Risk Legalization (Laundering) of Incomes Earned by Criminal Ways, Financing of Terrorism and Financing of Proliferation of Mass Destruction Weapons”. Apart from auditing firms, this Decree is binding for many other entities: professional agents of capital markets and organized commodity markets; suppliers of services related with circulation of virtual assets; lawyer’s offices, lawyer’s associations, lawyers performing activities on individual basis; notaries; business entities rendering legal services, services on asset management, accounting and consulting services on taxation issues, intermediary services on realty transactions, as well as ones engaged in cash trade of precious metals and precious stones and products made thereof, cultural treasures and/or rendering intermediary services in such activities; entities running a lottery and/or gambling. But the auditing activities differ from the ones listed above by its specifics. That is the reason why auditing firms need to develop their own intrafirm techniques on determining risk criteria and assessing risks in financial monitoring. It was found that an auditing firm was obliged to ensure identification, revaluation and updating of such risks at two levels: auditing firm (assessment of own risk profile) and client (assessment of client risk profile). The auditing firm management uses the principle of scaling: for a firm with a more sophisticated structure or a large number of clients, a formalized procedure for risk assessment may exist, involving several persons and assessing a larger number of activities, which may entail the occurrence of a larger number of risks. It was revealed that the estimate of risk profile for an auditing form, apart from the character and scale, is conditioned on the specifics of its clients’ activities, their geographic location and the location of the firm itself, banks with which the firm cooperates, methods of providing auditing services, such as distance ones, the availability of resource suppliers for carrying out auditor engagements. Based on normative instructions, an internal document for an auditing firm, “Risk Profile Assessment”, was developed, containing risk criteria and their assessment, information sources and conclusions on risk acceptance. The assessment needs to be performed by twelve systematized criteria in scores and involves four levels of risk: (i) low; (ii) medium; (iii) high; (iv) unacceptably high. A person performing the assessment needs to formulate and substantiate the conclusion about acceptability of risks by showing his/her irreconcilable stance to a possibility of legalization (laundering) of incomes earned by illicit ways, financing of terrorism or financing of the proliferation of mass destruction weapons. The proposed practical recommendations allow auditing firms to comply with the requirements of the law pertaining to financing monitoring, to submit, in due time, the information requested by the regulator, which is the Ministry of Finance of Ukraine, and to fix violations as soon as possible.